THE EFFECT OF APPLYING ANIMAL CARTOON PICTURES ON STUDENTS’ ACHIEVEMENT IN WRITING NARRATIVE TEXT - Hasanul Arifin Zul; Masitowarni Siregar (Universitas Negeri Medan, 2017)
This thesis is focused on the investigation of the effect of applying animal cartoon pictures on students’ achievement in writing narrative text. This study aims to find whether applying animal cartoon pictures significantly affect the students’ writing achievement or not. The data in this study were obtained by administering a written test. The population was the 2015/2016 first year (grade XI) of SMA Swasta Nusantara Lubuk Pakam and 66 students were taken as the sample by using random sampling. The sample was divided into two groups, experimental and control groups. The experimental group was taught by applying animal cartoon pictures while the control group without animal cartoon pictures (x = lecturing). The data were taken the scores from the pre-test and post-test to both experimental and control groups. These data were analyzed by using t-test. The result of computing the t-test obviously showed that t-observed is higher than t-table (5.21 >1,67) with the degree of freedom 64 (df =N-2) at the level significance 0,05 one tail test. It showed that the application of animal cartoon pictures significantly affected the students of SMA Swasta Nusantara Lubuk Pakam achievement in writing narrative text.